The Influence of Employee Involvement on Employee Performance Through Work Motivation at the Forestry Service of East Kalimantan Province - Riski Ananda, Riski Ananda; Istimaroh,; Fitriansyah, (Research in Management of Technology and Business, 2024)
ABSTRACTThis study aims to determine and analyze the effect of employee involvement on employee performance through work motivation at the East Kalimantan Provincial Forestry Service. The population of this study were employees of the East Kalimantan Provincial Forestry Service. This research uses descriptive quantitative type. This study obtained a sample of 156 respondents who were taken by probability sampling method using random sampling or all positions in the East Kalimantan Provincial Forestry Service. The data collection technique in this study used a questionnaire in the form of a Google Form. The data processing method in this study is to use IBM SPSS Version 26 and SmartPLS software version 4.0.2. The results of this study indicate that employee involvement has a positive and significant effect on employee performance, employee involvement has a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance, and employee involvement has a positive and significant effect on employee performance through work motivation.